BANTUAN ADVOKAT DALAM PENYELESAIAN WANPRESTASI (INGKAR JANJI) PADA PERJANJIAN BERBENTUK LISAN DI PENGADILAN - Azzahra Meutia; Hafni Zahra Charity; Sandra Ayu Wandira; Nawa Bathuta (JOURNAL SAINS STUDENT RESEARCH, 2025)
The resolution of default (wanprestasi) in verbal agreements is indeed an important issue in legal practice in Indonesia. Although verbal agreements are recognized by law, they often pose difficulties, especially in terms of proof when a breach occurs. The Supreme Court's decisions show that verbal agreements can still be debated in court, but the main challenge is the lack of written evidence to support the claims of the aggrieved party. Therefore, understanding the legal principles underlying verbal agreements is crucial to determine the appropriate legal steps. Lawyers play a vital role in resolving disputes related to default in verbal agreements. As legal professionals, lawyers assist clients in gathering relevant evidence, presenting legal arguments in court, and advising on ways to resolve disputes, both through litigation and alternative methods such as mediation. In this context, lawyers not only act as defenders but also as mediators who can help the parties reach a mutually beneficial agreement. This study uses a normative legal research methodology, which examines regulations and court decisions related to verbal agreements and default, to provide more effective solutions in handling disputes in the future.